2012
DOI: 10.1136/jech-2012-201564
|View full text |Cite
|
Sign up to set email alerts
|

Divergent associations of drinking frequency and binge consumption of alcohol with mortality within the same cohort

Abstract: Questions on drinking frequency and a specific question on binge drinking capture different effects of alcohol use on all-cause and CVD mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 19 publications
(26 reference statements)
1
28
0
1
Order By: Relevance
“…Among Finnish men, those who consumed six or more drinks per drinking occasion showed increased total mortality compared to those without such a pattern, independent of overall alcohol consumption (Kauhanen et al, 1997;Laatikainen et al, 2003). Further, among Norwegians ages 20-62 years, drinking five drinks or more per occasion, even when infrequent, was linked to increased 20-year total mortality (Graff-Iversen et al, 2013). Similarly, among U.S. adults 17 years of age and older followed for 9 years, drinking five or more drinks a day at any frequency predicted increased total mortality risk (Plunk et al, 2014).…”
Section: Heavy Episodic Drinking and Mortalitymentioning
confidence: 89%
“…Among Finnish men, those who consumed six or more drinks per drinking occasion showed increased total mortality compared to those without such a pattern, independent of overall alcohol consumption (Kauhanen et al, 1997;Laatikainen et al, 2003). Further, among Norwegians ages 20-62 years, drinking five drinks or more per occasion, even when infrequent, was linked to increased 20-year total mortality (Graff-Iversen et al, 2013). Similarly, among U.S. adults 17 years of age and older followed for 9 years, drinking five or more drinks a day at any frequency predicted increased total mortality risk (Plunk et al, 2014).…”
Section: Heavy Episodic Drinking and Mortalitymentioning
confidence: 89%
“…There is evidence that heavy episodic (binge) drinking, which results in exposure of tissues to high levels of alcohol, is particularly harmful 81, 87, 88 . Binge drinking is generally defined as a man consuming 5 standard drinks within 2 hours; women are typically smaller and have a lower percentage of body water, so 4 standard drinks can reach similar alcohol levels.…”
Section: Genetics Of Alcohol-associated Diseasesmentioning
confidence: 99%
“…These alcohol-attributable costs exceed 1% of the gross national product of high-and middle-income countries, making pathological alcohol use one of the largest avoidable risk factors for the global burden of disease [1]. Studies have reported that alcohol use is associated with cardiovascular disease (CVD), although there is debate about these conclusions [2][3][4][5][6][7][8]. However, there is the lack of updated information that specifically examines the status of alcohol consumption in China, which has been experiencing rapid economic progress and epidemiologic transitions that are often associated with an increase in CVD [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%